Dependência espacial da estabilidade de agregados e matéria orgânica do solo em cambissolo sob cultivo de cana de açucar - de Oliviera, Ivanildo Amorim [UNESP]; Campos, Milton César Costa; Eleotério Aquino, Renato [UNESP]; Freitas, Ludmila [UNESP]; Pinheiro da Silva, Douglas Marcelo (My University, 2013)
The soil management system can modify the natural distribution of the soil attributes and, consequently, the variability of the soil aggregation and organic matter content. Thus, the aim of this work was to evaluate the aggregate stability and organic matter content spatial distribution on a Haplic Cambisol under sugar cane cultivation in the Southern Amazonas State, Brazil. A 70 x 70 m square mesh, with regular 10 meters intervals, was designed over the cultivation area, resulting in 64 sample points. Soil blocks with preserved structure were collected at 0.0-0.2 m depth in order to analyze the aggregate stability and organic matter content. The data were submitted to the descriptive and geostatistical analysis. The soil attributes presented a spatial dependence structure and the greater range was observed for the mean weighted diameter and aggregate class <1.00 mm. Also, there is a spatial relation among the mean geometric diameter, mean weighted diameter and aggregate classes (> 2.00 and 2.00-1.00 mm).
Spatial dependence of the aggregate stability and organic matter in a cambisol under sugar cane cultivation
Keywords: Geostatistics; Soil aggregation; Soil physical attributes